Experimental study for sand bricks with clinker as partial replacement for fine aggregate with ratio of 15% with rice husk of 10% , 20 % and 30% - Muhammad Rasydan, Kamarudin (2019)
This research has aims to study for sand bricks with clinker as partial replacement for fine aggregate with ratio of 15% with rice husk of 10%, 20% and 30%. RH is a waste material that produce after harvesting the paddy and being disposed while POC is a by-product from the processing stages of palm oil goods. By relating to this study, the POC and raw RH have the same texture and physical as normal sand. The field of studies covers crucial parameters in determining the compressive strength, flexural strength water absorption ability and density. A total 216 sand bricks with dimension of 225mm length, 113 width and 75mm depth were prepared and been divided into four groups according to different type of testing. The compression test used 120 bricks and flexural test used 72 bricks while water absorption test and density test are same with 24 bricks. All the sand bricks samples in each of the test had four different replacement of RH percentages. There were 10%, 20%, 30% and the control mixture. All sample are divided equally and cured in air and water curing for 28, 60 and 90 days before testing. The samples at 60 days of curing with RH 10% are shows the best mixture for both type of curing. The final result indicate that all sample are achieved the minimum compressive and flexural strength. The study finally demonstrated that cement sand brick with clinker and RH as partial replacement for fine aggregate get better result.